Attaining the 2030 sustainable development goal of life on land - Birdthistle, Naomi (Emerald Publishing Limited, 2024)
Attaining the 2030 Sustainable Development Goal of Life on Land focuses on Sustainable Development Goal number fifteen (SDG#15): to protect, restore, and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertification, and halt and reverse land degradation, and halt biodiversity loss. Examining family businesses in Australia, Honduras, Chile, and the UAE, each chapter case study presents a unique perspective from their respective country, analysing how SDG#15 translates into promoting a sustainable use of our ecosystems and preserving biodiversity. The case studies presented generate insights and key takeaways into the role of family businesses in fostering a flourishing global ecosystem. The United Nations' (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editor Naomi Birdthistle brings together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations and philanthropic centres - this book series equally appeals to those with a general interest in entrepreneurship and business.
Includes index.
Keywords: Business ethics.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books